External control of fluoridation of public water supplies of the city of Jaguaribara, Ceará, Brazil - Daniel Fernandes Peixoto; Karla Pinheiro Alencar; Raniel Fernandes Peixoto; Consuelo Fernanda Macedo de Sousa; Fábio Correia Sampaio; Franklin Delano Soares Forte (Universidade de Fortaleza, 2012)
Objective: To monitor the levels of fluoride (F) in public water supplies in the city of Jaguaribara, Ceará, Brazil. Methods: Water samples were collected from the urban area, at three different points. Samples were collected twice a month, from August 2010 to July 2011. The samples were analyzed in triplicate, using the combined electrode connected to a meter, previously calibrated with standards containing 0.2 to 6.4 ppm F, with Tisab II. Data was analyzed by three criteria: I (Brazil, 1975), II (Ramires et al., 2006) and III (Technical Consensus, 2011). results: Among a total of 72 water samples, we observed an average of 0.55 (± 0.19) ppm F, median of 0.61. According to Criterion I, acceptable levels of fluoride were found in 47.2% of samples, while 44,4% were underfluoridated (<0.60 ppm F) and 8,3% were overfluorinated. For criterion II, it was observed that 36.1% of the samples were acceptable (<0.55 ppm F) and 63.9% were into acceptable limits (0.55 and 0.84 ppm F), with no overfluorinated sample (> 0.84 ppm F). Based on criterion III, 25% of samples showed negligible risk and benefits concerning dental fluorosis and prevention of dental caries, while 11.1% of the samples presented low risk and benefit and 63.9% pointed to low risk and maximum benefit. Conclusions: Altered levels of fluoride were observed in public water supplies in the studied period. It is suggested the need to improve operational control and also the external control of water fluoridation in Jaguaribara, Ceará, Brazil.